The breath of the living: inspirations in Art and Science (DAPesquisa, 2022)
In this article I recall the activities and impulses that resulted in the air project, which was carried out by the collaborative duo asikainen&macêdo. Through this work, I investigate the complex political, cultural, economic, scientific, social and aesthetic network of relationships that involve the issue of deforestation, global warming and scientific negationism. During two residences in the forests of Brazil and Finland, asikainen&macêdo established dialogues with scientists who develop research on climate change, for the construction of this artistic project that continues to point us to increasingly urgent problems.
Keywords: Art and science; Contemporary art; global warming